2011
DOI: 10.1037/a0021643
|View full text |Cite
|
Sign up to set email alerts
|

Escaping affect: How motivated emotion regulation creates insensitivity to mass suffering.

Abstract: As the number of people in need of help increases, the degree of compassion people feel for them ironically tends to decrease. This phenomenon is termed the collapse of compassion. Some researchers have suggested that this effect happens because emotions are not triggered by aggregates. We provide evidence for an alternative account. People expect the needs of large groups to be potentially overwhelming, and, as a result, they engage in emotion regulation to prevent themselves from experiencing overwhelming le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
343
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(365 citation statements)
references
References 76 publications
14
343
2
6
Order By: Relevance
“…In addition, this research contributes to a growing body of work that highlights how, despite the prosocial benefits it often affords, compassion can sometimes lead individuals to act contrary to what is truly in others' best interests (e.g., Cameron & Payne, 2011;Slovic, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this research contributes to a growing body of work that highlights how, despite the prosocial benefits it often affords, compassion can sometimes lead individuals to act contrary to what is truly in others' best interests (e.g., Cameron & Payne, 2011;Slovic, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Compassion is evoked by witnessing or learning about others' physical or emotional pain (Batson et al, 1997;Condon & DeSteno, 2011;Eisenberg et al, 1989;Stellar, Cohen, Oveis, & Keltner, 2014;Stellar, Feinberg, & Keltner, 2014;Stellar, Manzo, Kraus, & Keltner, 2012;Van Kleef et al, 2008) or victimization (Cameron & Payne, 2011;Valdesolo & DeSteno, 2011a), and by viewing depictions of suffering others such as homeless or malnourished people (Oveis et al, 2009;Oveis, Horberg, & Keltner, 2010).…”
mentioning
confidence: 99%
“…The influence of modulatory processes on emotions evoked in response to another's distress, particularly emotion regulatory processes, may be important for biasing an individual toward a concerned and compassionate response rather than personal distress (Batson et al, 1983;Batson et al, 1987;Eisenberg et al, 1989;Klimecki et al, 2014). However, another threat to a concerned prosocial response is regulation of empathic affect resulting in apathy (Cameron and Payne, 2011). The current studies thus sought to examine the role of emotion regulatory appraisals in promoting prosocial helping behavior, first in a proof of concept test of an empathic emotion regulation task and then in an extension of this concept to extraordinary altruists.…”
mentioning
confidence: 99%
“…Cameron and colleagues (Cameron and Payne, 2011) have highlighted that emotion regulation can also inhibit empathy and prosociality, and their "collapse of compassion" studies have found that higher trait emotion regulation skill and also instructed emotion regulation both resulted in decreased concern for multiple victims. Similarly, Lockwood and colleagues (Lockwood et al, 2014) have found that trait empathy only predicts prosocial tendencies for those with low to moderate trait reappraisal tendency.…”
mentioning
confidence: 99%
See 1 more Smart Citation